Association of TLR4-T399I Polymorphism with Chronic Obstructive Pulmonary Disease in Smokers - Matthaios Speletas; Vassiliki Merentiti; Konstantinos Kostikas; Kyriaki Liadaki; Markos Minas; Konstantinos Gourgoulianis; Anastasios E. Germenis (Clinical and Developmental Immunology)
Tobacco smoking has been considered the most important risk factor for chronic obstructive pulmonary disease (COPD) development. However, not all smokers develop COPD and other environmental and genetic susceptibility factors underlie disease pathogenesis. Recent studies have indicated that the impairment of TLR signaling might play a crucial role in the development of emphysema. For this purpose we investigated the prevalence and any possible associations of common TLR polymorphisms (𝑇𝐿𝑅2-R753Q, 𝑇𝐿𝑅4-D299G, and 𝑇𝐿𝑅4-T399I) in a group of 240 heavy smokers (>20 pack years), without overt atherosclerosis disease, of whom 136 had developed COPD and 104 had not. The presence of 𝑇𝐿𝑅4-T399I polymorphism was associated with a 2.4-fold increased risk for COPD development (𝑃=.044), but not with disease stage or frequency of exacerbations. Considering that infections contribute to COPD and emphysema pathogenesis, our findings possibly indicate that dysfunctional polymorphisms of innate immune genes can affect the development of COPD in smokers. Although this finding warrants further investigation, it highlights the importance of impaired innate immunity towards COPD development.